Instigating Learning Management In Building Students' Ecological Awareness At Madrasah Ibtidaiyah Pamekasan Madura - Moh. Asy’ari (JIEMAN: Journal of Islamic Educational Management, 2023)
Management is a determining factor in building good quality education, learning Management as a process of face-to-face implementation between teachers and students and learning resources to provide stimulus to create knowledge, experience and self-actualization in real life as self-implementation. This research aims to describe the planning, organization, implementation and evaluation of learning management in building students' ecological awareness at Madrasah Ibtidaiyah along with finding out the factors that support and hinder the implementation of environmental learning management. The research method uses qualitative with a phenomenological type of research subject, the head of the madrasah, teachers and students, data obtained by interviews, observation and documentation. The research results are first, learning management in building students' ecological awareness is 1) integrated into several subjects such as science, social studies, PKN and religion which are adjusted to learning planning. 2) organizing environmental learning, the head of the madrasah instructs the teachers. 3) learning is carried out in the classroom and outside the classroom. 4) learning evaluation in building students' ecological awareness is direct observation and providing guidance for those who do not comply with the rules. Manajemen merupakan faktor penentu dalam membangun mutu Pendidikan yang baik, Manajemen pembelajaran sebagai suatu proses pelaksanaan tatap muka antara guru dan anak didik serta sumber belajar yang memberikan stimulus agar supaya tercipta pengetahuan, pengalaman dan aktualisasi diri pada kehidupan nyata sebagai implementasi diri. Penelitian ini bertujuan untuk mendeskripsikan perencanaan, pengorgaisasian, pelaksanaan dan evaluasi manajemen pembelajaran dalam membangun kesadaran ekologis anak didik di Madrasah Ibtidaiyah beserta untuk mengetahui faktor-faktor yang mendukung dan penghambat terhadap implementasi manajemen pembelajaran lingkungan hidup. Metode penelitian menggunakan kualitatif dengan jenis fenomenoligi subjek penelitian kepala madrasah, para guru beserta anak didik data diperoleh dengan wawancara, observasi dan dokumentasi.  Hasil penelitian adalah 1) perencanaan manajemen pembelajaran dalam membangun kesadaran ekologis anak didik di integrasikan pada beberapa mata Pelajaran seperti IPA, IPS, PKN dan agama yang disesuaikan dengan materi pembelajaran. 2) pengorganisasian pembelajaran lingkungan hidup kepala madrasah mengintruksikan kepada para guru. 3) pelaksanaan pembelajaran dilakukan dalam kelas dan luar kelas. 4) evaluasi pembelajaran dalam membangun kesadaran ekologis anak didik yaitu dengan pengamatan langsung dan pemberian pembinaan bagi yang tidak patuh pada aturan.